On the incorporation of iron into hexagonal barium titanate: I. electron paramagnetic resonance (EPR) study. (27th September 2018) - Böttcher, R; Langhammer, H T; Kücker, S; Eisenschmidt, C; Ebbinghaus, S G
Abstract: Electron paramagnetic resonance (EPR) investigations of BaTiO3 + 0.04 BaO + x /2 Fe2 O3 (0.007 ⩽ x ⩽ 0.05) ceramics and BaTi0.98 Fe0.02 O3 single crystals were performed to study the incorporation of Fe ions in the hexagonal 6H-BaTiO3 lattice and their defect properties. The samples were characterized by x-ray diffraction and wavelength-dispersive x-ray electron probe microanalysis. EPR spectra were recorded both in X- and Q-bands at room temperature. Angle-dependent single crystal EPR investigations and simulations of the ceramic powder EPR spectra revealed three different centers, which can be attributed to Fe 3+ ions incorporated on crystallographically different Ti sites. Only one of them was already known before. Two spectra with axial symmetry belong to isolated Fe 3+ ions incorporated at Ti(1) sites (exclusively corner-sharing oxygen octahedra) and Ti(2) sites (face-sharing octahedra). The difference of their spectral parameters arises from the different trigonal distortions of the two types of octahedra. The third spectrum has orthorhombic symmetry and is caused by Fe 3+ centers associated with a nearest-neighbor charge-compensating oxygen vacancy. A model for the location of this associate is proposed.